2020
DOI: 10.1016/j.jmatprotec.2020.116746
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional detection of subsurface damage in silicon wafers with polarized laser scattering

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…They suggested that the photoelasticity could be minimized by aligning the polarization direction to a principal stress direction. They further revealed that both the SSD depth and distribution density in a ground silicon wafer affects the polarized laser scattering detection, with SSD depth being the dominant factor [19]. PLS provides a potential for detecting SSD in monocrystalline silicon.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…They suggested that the photoelasticity could be minimized by aligning the polarization direction to a principal stress direction. They further revealed that both the SSD depth and distribution density in a ground silicon wafer affects the polarized laser scattering detection, with SSD depth being the dominant factor [19]. PLS provides a potential for detecting SSD in monocrystalline silicon.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…More related research must be conducted on Active Wafer Centering abroad, and the AWC algorithm requires only two sensors to obtain the relative distance between the wafer center and the manipulator. This paper focuses on the motion control and AWC wafer calibration algorithm for semiconductor equipment handling robots, aiming to achieve fast, stable, and efficient transmission and operation in the manufacturing environment [13][14][15][16][17][18][19]. The paper analyzes the transmission mechanism and kinematics of the semiconductor handling robot using the geometric method, and the results form the basis of the AWC algorithm.…”
Section: Introductionmentioning
confidence: 99%